Dynamic distinctions in the Na+/Ca2+ exchanger adopting the inward- and outward-facing conformational states - Giladi, Moshe; van Dijk, Liat; Refaeli, Bosmat; Almagor, Lior; Hiller, Reuben; Man, Petr; Forest, Eric; Khananshvili, Daniel (The Journal of biological chemistry, 2017)
Na+/Ca2+ exchanger (NCX) proteins operate through the alternating access mechanism, where the ion-binding pocket is exposed in succession either to the extracellular or the intracellular face of the membrane. The archaeal NCX_Mj (Methanococcus jannaschii NCX) system was used to resolve the backbone dynamics in the inward-facing (IF) and outward-facing (OF) states by analyzing purified preparations of apo- and ion-bound forms of NCX_Mj-WT and its mutant, NCX_Mj-5L6-8. First, the exposure of extracellular and cytosolic vestibules to the bulk phase was evaluated as the reactivity of single cysteine mutants to a fluorescent probe, verifying that NCX_Mj-WT and NCX_Mj-5L6-8 preferentially adopt the OF and IF states, respectively. Next, hydrogen-deuterium exchange-mass spectrometry (HDX-MS) was employed to analyze the backbone dynamics profiles in proteins, preferentially adopting the OF (WT) and IF (5L6-8) states either in the presence or absence of ions. Characteristic differences in the backbone dynamics were identified between apo NCX_Mj-WT and NCX_Mj-5L6-8, thereby underscoring specific conformational patterns owned by the OF and IF states. Saturating concentrations of Na+ or Ca2+ specifically modify HDX patterns, revealing that the ion-bound/occluded states are much more stable (rigid) in the OF than in the IF state. Conformational differences observed in the ion-occluded OF and IF states can account for diversifying the ion-release dynamics and apparent affinity (Km ) at opposite sides of the membrane, where specific structure-dynamic elements can effectively match the rates of bidirectional ion movements at physiological ion concentrations.
Keywords: calcium transport; pumpa pro výměnu sodíku a vápníku; Protein Stability; Recombinant Proteins; Calcium; exchanger; archeální proteiny; mutace; Deuterium Exchange Measurement; vazebná místa; interakční proteinové domény a motivy; Sodium-Calcium Exchanger; ligandy; stabilita proteinů; výpočetní biologie; vápník; transporter; cystein; Ligands; membrane transport; apoproteiny; sodík; vodík-deuteriová výměna; hydrogen exchange mass spectrometry; membrane protein; Mutagenesis, Insertional; Amino Acid Substitution; molekulární modely; peptidové fragmenty; Methanocaldococcus; rekombinantní proteiny; Models, Molecular; Binding Sites; Cell Membrane; Protein Interaction Domains and Motifs; kinetika; Apoproteins; Sodium; calcium; sodium-calcium exchange; konformace proteinů; calcium-binding protein; inzerční mutageneze; substituce aminokyselin; buněčná membrána; Protein Conformation; Archaeal Proteins; Mutation; Peptide Fragments; Cysteine; Kinetics; Computational Biology